(untitled) (Baghdad Science Journal, 2023)
The study involved preparing a new compound by combining Schiff bases generated from compounds for antipyrine, including lanthanide ions (lanthanum, neodymium, erbium, gadolinium, and dysprosium). The preparation of the ligand from condensation reactions (4-antipyrinecarboxaldehyde with ethylene di-amine) at room temperature, and was characterization using spectroscopic and analytical studies ( FT-IR, UV-visible spectra, 1H-NMR, mass spectrometry, (C.H.N.O), thermogravimetric analysis (TGA), in addition to the magnetic susceptibility and conductivity measurement of the synthesis complexes, among the results we obtained from the tests, we showed that the ligand behaves with the (triple Valence) lanthanide ions, the multidentate behavior through two oxygen atoms of the carbonyl group and two nitrogen atoms of the azomethine group with all the prepared complexes in a molar ratio (1:1). The participation of six groups of bidentate nitrate in the coordination and indicating that their complexes have values of magnetic moment and paramagnetic character and, based on the results of those measurements, the geometrical shape of the complexes was proposed. The biological activity of the prepared complexes was studied using the antibacterial activity, as the results of its effectiveness showed the direction of the bacteria used (Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Klebsiella pneumoniae) at the concentration of 1×10-3M